Models, methods and means of ontology development of cyclic signal processing - Lupenko, S. A.; Lytvynenko, Ya. V.; Zozulya, A. M.; Chizoba, N. K.; Volyanyk, O. V. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2021)
The paper presents the construction of conceptual and formal models of ontology in the subject area "Modeling and processing of cyclic signals based on the theory of cyclic functional relations". There is implemented the ontology of mathematical modelling of cyclic signals, namely, the ontology of cyclic functional relations in the OWL DL language in Protégé. The proposed ontology has allowed to present the theory of cyclic functional relations in machine-interpretive form, which allows to serve as a basis for the development of onto-oriented information systems for modeling, generation, processing (analysis, forecasting, decision making) of cyclic signals.